Improving Early Childhood Creativity Through Brain Gym Method - Bayti Hasnani; Cahniyo Wijaya Kusuma; Nilawati Tadjuddin (Journal of Early Childhood Development and Education, 2024)
The purpose of this study is to ascertain how Brain Gym exercises affect young children's creativity in Raudhatul Athfal Ulul Albab Tulung Batuan Kotabumi North Lampung. This study employs an experimental design, specifically the Nonequivalent Control Group Design, which is a quasi-experimental research methodology. Instruments for gathering data make use of documentation and observation. Utilizing the formula for product moment correlation, evaluate the validity of the instrument. Use the Cronbach's alpha calculation to assess the instrument's dependability. A normalcy test using the Kolmogorov-Smirnov formula. Use the F test to determine homogeneity. Use the independent t test to evaluate the hypothesis. The hypothesis test results indicate that there is a relationship between brain gym activities and early childhood creativity in Raudhatul Athfal Ulul Albab Tulung Batuan Kotabumi North Lampung. Specifically, the value of tcount > ttable, or 3.179 > 2.013, indicates that this relationship exists.